TR9 Resuscitative hysterotomy training for interprofessional teams using a fresh frozen cadaver with synthetic uterine tissues. (November 2018) - Cooper, Emily; Hammett, Owen; Kellett, Suzie; Halls, Mark; Umranikar, Sameer; Hyde, Phil
Abstract : Although somewhat rare, worldwide 1 in every 30 000 women will have a cardiac arrest during their pregnancy. For the teams of clinicians providing care for these women, it is known that acting quickly to recognise the need for, decide and carry out a resuscitative hysterotomy is associated with improved survival outcomes for both mother and baby (Eldridge and Ford 2016, Smith et al . 2012). Alongside recommendation that the fetus be delivered within 1 min of commencing the resuscitative hysterotomy current literature recommends training in order to improve efficiency, confidence and reduce human factors (Eldridge and Ford 2016, Smith et al . 2012) Prepared within the anatomy lab using a female fresh frozen cadaver, a preterm mannequin, umbilical cord and placenta is inserted into a artificial amniotic sack with fluid which is placed into a synthetic uterus and positioned into the cadaver using a high incision distal to the diaphragm. Prior to undertaking the procedure using the hybrid model, inter-professional teams (incorporating nurses, doctors, paramedics and ODP's) are taught the indications, contra-indications as well as the procedure by a subject matter expert. This is demonstrated on the hybrid model, to enable candidates to see the procedure being carried out. The teams are given the opportunity to practice on both the hybrid model and other synthetic models and undertake high fidelity simulation. This provides them the opportunity to practice dissecting through the layers of tissue and deliver the fetus and placenta, and the crew resource management required in managing two patients. This method of training interprofessional teams aims to improve the teams confidence in order to quickly make the decision to carry out a resuscitative hysterotomy, and provide them with the opportunity to practice carrying out the procedure on a high fidelity hybrid human/synthetic model. The development of the hybrid model for training has been well received among prehospital and emergency department teams within the Wessex, UK region, with an interest to expand the audience to obstetric teams and outside of the Wessex region. In addition to the teams being able practice their decision making and the technical procedure, the complexities of managing a highly stressful and emotive situation is mentally rehearsed. References: Eldridge A, For, R. Perimortem caesarean deliveries. International Journal of Obstetric Anesthesia2016;27:46–54. Smith A, Edwards S, Siassakos D. Effective team training to improve outcomes in maternal collapse and perimortem caesarean section. Resuscitation2012;83(10):1183–4.